SEKOLAH PENGARUH PENDIDIKAN, PELATIHAN, DAN PENGALAMAN MENGAJAR TERHADAP KINERJA GURU DI SMK YAPIM TARUNA - BETI RIA JUMIRA NASUTION; Edi Siregar; yosi Stefhani (Pasca Sarjana Universitas Satya Negara Indonesia, 2025)
ABSTRACTThis study aims to describe the influence of education, training, and teaching experience on teacher performance at SMK Yapim Taruna. The study uses a quantitative approach with a causal design through the distribution of questionnaires and literature review as data collection methods. The research sample consists of all honorary teachers, totaling seventy-one individuals. The results indicate that education, training, and teaching experience collectively influence teacher performance. However, when considered separately, education and training are proven to enhance performance, while teaching experience has a distinct impact. These findings emphasize that improvements in teacher performance are not solely determined by experience but are more significantly supported by the quality of education and training programs received. The novelty of this study lies in its comprehensive analysis of honorary teachers in vocational schools, a group that has previously received little attention in teacher performance studies. The implications of this research can serve as a basis for schools in designing more targeted competency development programs, particularly by strengthening formal education and continuous training as key strategies to improve teacher performance quality in vocational schools. Keywords: teacher education, training, and teaching experience, teacher performance